Envisioning a future for Bornean orangutans: Conservation impacts of action plan implementation and recommendations for improved population outcomes - Julie Sherman; Marc Ancrenaz; Maria Voigt; Felicity Oram; Truly Santika; Serge Wich; Erik Meijaard (Society for Indonesian Biodiversity, 2020)
Abstract. Sherman J, Ancrenaz M, Voigt M, Oram F, Santika T, Wich S, Meijaard E. 2020. Envisioning a future for Bornean orangutans: Conservation impacts of action plan implementation and recommendations for improved population outcomes. Biodiversitas 21: 465-477. Populations of the Critically Endangered Bornean orangutan (Pongo pygmaeus) are declining despite more than 10 years of conservation action plan implementation. Here we analyzed the impacts on species' population and habitat from orangutan conservation strategies implemented between 2007 and 2017. We also assessed data on investments into orangutan conservation, orangutan population trends and landcover change in orangutan range between 2007 and 2017. Diverse strategies addressed the range of threats to orangutans but were not implemented at scales that impacted species’ level populations and habitats. Since 2007 orangutan populations and forests across orangutan range have declined, with orangutan killing and deforestation as the major drivers of loss. Protected areas have increased since 2007, notably in Malaysian range states and in Central Kalimantan, Indonesia. However, 80% or tens of thousands of orangutans live outside protected areas in Kalimantan alone. Our results underscore scientific findings that have demonstrated this species’ resiliency and modified previous understanding of their habitat use. Orangutans are regularly found using agriculture landscapes (acacia, oil palm, and timber plantations), and exploited forests. This plasticity must be considered to design more effective orangutan conservation strategies. We need to revise the notion of “orangutan habitat” to extend beyond forests alone, incorporating all landscapes where P. pygmaeus can be found. Orangutans cannot survive in exclusively monoculture production areas; they need some natural forest to fulfill their ecological requirements. However, individuals surviving in isolated forest patches or mosaic landscapes play an important role in sustaining the long-term viability of the local metapopulation through provision of crucial genetic, reproductive and socioecological connectivity. Our findings suggest removing these individuals through translocations weakens overall metapopulation health. All necessary efforts must be made to maintain individuals in isolated forest patches or mosaic landscapes in order to support healthy metapopulations. Improved orangutan population outcomes will require addressing habitat connectivity at the landscape level, incorporating both non-forested and anthropogenically modified areas, and developing efficient management strategies for human and orangutan co-existence within these multiple-use landscapes.